DEKONSTRUKSI STRUKTUR POLITIK PUSAT DAN PENGUATAN SUMBERDAYA MOBILISASI DI WILAYAH PINGGIRAN SEBAGAI BASIS MUNCULNYA GERAKAN PETANI DI LAMPUNG - Hartoyo, Hartoyo; Soetarto, Endriatmo; Dharmawan, Arya Hadi; Lawang, Robert M.Z (Jurnal AGRISEP, 2010)
Contemporary  peasant  movements   are still important to be studied, especially under the reformation era (or the democracy transition).  The objective of this study were to analyze the relationship  of the determinant  factors on peasant  movement. Qualitative  approach was applied in  this  case. Data  was  employed in triangulation using  dept  interviews, documentations,   and secundary data. Result showed that the combination   of political opportuniiq structure and structure of resource  mobilization   affords  groups a certain structural  potential for action, they remain, in the absence of two other factors,  insuffisient to account for peasant movement.  The two factor were the sub-culture  of peasant opposition as the antecedent factor and collective framing  as the mediating factor.